АМАЛИЙ ДАСТУРЛАР ОРҚАЛИ МАТЕМАТИКАНИ ЎҚИТИШ - Мамадиёров, Ж.Б. (SCIENCE and SOCIETY, 2020)
The article describes the methods of teaching mathematics using information technologies. They include computer training systems, including Flash software, language HTML, e-textbooks, as well as methods of using modern information technologies.
Keywords: Flash program; language HTML; electronic textbooks; innovative technologies in education; information and communication technologies; modern computer information technologies